1999
DOI: 10.1002/(sici)1097-0355(199922)20:2<188::aid-imhj6>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Attachment disturbances in infants born subsequent to perinatal loss: A pilot study

Abstract: Mothers who have lost a baby in the perinatal period may experience relationship disturbances with infants born subsequently. This study involved mothers who had delivered a child within 19 months of losing a baby in the perinatal period. Mothers were assessed 2 months after the loss with a clinical interview. When the child born subsequent to the loss was 12 months old, the mother–child attachment relationship was assessed, and 45% of the infants had disorganized attachments to their mothers. This was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
2
34
0
3
Order By: Relevance
“…Limited available data suggest that mothers may have more concerns about and greater difficulty managing the needs of a child born after a prenatal loss; 19,28 also, 12-month-old infants born following prenatal loss were reported to show higher rates of disorganised attachment patterns to their mothers than children born into families without a loss history. 29,30 Thus, even if there is no persistence of mood disturbance into the postnatal period, there may still be adverse effects of a previous prenatal loss on the parent–child relationship and child outcomes. This possibility requires further attention.…”
Section: Discussionmentioning
confidence: 99%
“…Limited available data suggest that mothers may have more concerns about and greater difficulty managing the needs of a child born after a prenatal loss; 19,28 also, 12-month-old infants born following prenatal loss were reported to show higher rates of disorganised attachment patterns to their mothers than children born into families without a loss history. 29,30 Thus, even if there is no persistence of mood disturbance into the postnatal period, there may still be adverse effects of a previous prenatal loss on the parent–child relationship and child outcomes. This possibility requires further attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence to suggest that some mothers seem to show decreased attachment in subsequent pregnancies. These behaviors could serve as a protective and even practical approach women use to deal with the uncertainty of the outcome of their pregnancy What is unknown and perhaps more significant is to determine the effect of these behaviors on paternal attachment in the newborn period and beyond, especially because earlier and limited research in this area has shown problems with attachment (Heller & Zeanah, 1999) and disrupted parenting (Forrest, Standish, & Baum, 1982; Hunfeld et al, 1997; Phipps, 1985-86) for infants born after a subsequent pregnancy. Investigators in this review have noted the importance of future research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…To date, three studies have reported on the effect of pregnancy loss on infant attachment. Goldberg et al found that at 1 year all of five surviving twins had a secure relationship with their mothers, but this study did not assess infant disorganisation (Goldberg, Perrotta, Minde & Carter, 1986), whereas an uncontrolled study of 19 infants born subsequent to perinatal loss found 45 % to be disorganised at 1 year (Heller & Zeanah, 1999). A study of 30 women who had previously miscarried in early pregnancy did not report on infant attachment categories, and found low levels of unresolved classification in the mothers, but observed an association between mothers' scores on the unresolved scale of the Adult Attachment Interview and scores for infant disorganisation (BakermansKranenburg, .…”
Section: Introductionmentioning
confidence: 85%